New syllabus primary mathematics 3 - Yee, Dr. Foong Pul (Karachi: Oxford University Press., 2024)
New Syllabus Primary Mathematics 3 is a comprehensive textbook designed to build strong mathematical foundations for students in Grade 3. The book covers key topics such as addition, subtraction, multiplication, division, fractions, and geometry, with a focus on developing problem-solving skills and logical thinking. Each chapter is structured with clear explanations, step-by-step examples, and practice exercises to reinforce learning. The textbook incorporates real-life applications and interactive activities to make math engaging and accessible for young learners, providing them with the tools they need to succeed in more advanced mathematical studies.